Therapeutic Hypothermia for Neonatal Hypoxic–Ischemic Encephalopathy – Where to from Here? - Davidson, Joanne O.; Wassink, Guido; van den Heuij, Lotte G.; Bennet, Laura; Gunn, Alistair J. (Frontiers in Neurology, 2015)
Hypoxia-ischemia before or around the time of birth occurs in approximately 2/1000 live births and is associated with a high risk of death or lifelong disability. Therapeutic hypothermia is now well established as standard treatment for infants with moderate to severe hypoxic-ischemic encephalopathy but is only partially effective. There is compelling preclinical and clinical evidence that hypothermia is most protective when it is started as early as possible after hypoxia-ischemia. Further improvements in outcome from therapeutic hypothermia are very likely to arise from strategies to reduce the delay before starting treatment of affected infants. In this review we examine evidence that current protocols are reasonably close to the optimal depth and duration of cooling, but that the optimal rate of rewarming after hypothermia is unclear. The potential for combination treatments to augment hypothermic neuroprotection has considerable promise, particularly with endogenous targets such as melatonin and erythropoietin and noble gases such as xenon. We dissect the critical importance of preclinical studies using realistic delays in treatment and clinically relevant cooling protocols when examining combination treatment, and that for many strategies overlapping mechanisms of action can substantially attenuate any effects.